Pressure-induced enhancement in the superconductivity of ZrTe3. (29th August 2018) - Gu, Kemin; Susilo, Resta A; Ke, Feng; Deng, Wen; Wang, Yanju; Zhang, Lingkong; Xiao, Hong; Chen, Bin
Abstract: We report the superconductivity enhancement of ZrTe3 on compression up to 33 GPa. The superconducting transition occurs above 4.1 GPa and the superconducting temperature ( T C ) increases with pressure in further compression, reaching a maximum of 7.1 K at 28 GPa. An anomalous change of superconducting temperature is seen in the compression above 21 GPa. No structural phase transition is observed in the whole compression up to 36 GPa, but a subtle change in structural parameter is seen between 17–19 GPa, which seems relevant to the anomalous increase in the superconducting temperature. First-principle calculations reveal that the density of states at the Fermi level increases with pressure, which explains the enhancement of T C in ZrTe3 under compression.